Peran Stres Kerja dan Komitmen Organisasional pada Pengaruh Konflik Pekerjaan-Keluarga terhadap Kinerja Pegawai Wanita Rumah Sakit Jiwa Provinsi Kalimantan Barat - Rizky Fauzan (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2022)
This study to examine and analyze the role of mediation work stress and organizational commitment on the influence of work-family conflict on the performance of female employees of the Rumah Sakit Jiwa Provinsi Kalimantan Barat. This type of research is explanatory research with a quantitative approach. The population in this study were female employees of the Rumah Sakit Jiwa Provinsi Kalimantan Barat. The total sample of 124 respondents was chosen by purposive sampling, then processing data using path analysis. The results of the first model study show that work-family conflict variables have a positive and significant effect on work stress. The results of the study for the second model show that work-family conflict variables have a negative and not significant effect on organizational commitment while work stress has a positive and significant effect on organizational commitment. The results of the study for the third model show that work-family conflict variables and organizational commitment have a positive and significant effect on performance, while work stress has a negative and not significant effect on employee performance